Antidepressant Poisoning Trends in Pediatric Intensive Care: A Comparative Study of New- and Old-Generation Antidepressants. Issue 2 (16th March 2023) - Gurbanov, Anar; Kandemir, Hande; Gurbanova, Lala; Gün, Emrah; Botan, Edin; Balaban, Burak; Kahveci, Fevzi; Özen, Hasan; Uçmak, Hacer; Özdemir, İhsan; Havan, Merve; Tekin, Deniz; et al.
Abstract: Purpose/Background: This study aimed to compare the frequency, clinical findings, treatment practices, and outcomes of toxicity to old-generation (OG) and new-generation (NG) antidepressants in our pediatric intensive care unit (PICU) by year-to-year. Methods/Procedures: The study included patients hospitalized for antidepressant poisoning during the 11-year period of January 2010 through December 2020. Antidepressants were classified as OG and NG. The groups were compared in terms of patient demographic characteristics, type of poisoning (accidental/suicidal), clinical findings, supportive and extracorporeal treatments received, and outcomes. Findings/Results: The study included 58 patients (NG, n = 30; OG, n = 28). The median age of the patients was 178 months (range, 13.6–215 months) and 47 patients (81%) were female. Patients admitted for only antidepressant poisoning constituted 13.3% of all poisoning cases (58/436). Of these, 22 cases (37.9%) were accidental and 36 (62.3%) were suicidal. The most common cause of poisoning was amitriptyline (24/28) in the OG group and sertraline (13/30) in the NG group. Neurological symptoms were significantly more common in the OG group (76.2% vs 23.8%), while gastrointestinal involvement was more common in the NG group (82% vs 18%; P = 0.001 and P = 0.026, respectively). Old-generation antidepressant poisoning was associated with more frequent intubation (4 vs 0 patients, P = 0.048) and longer length of PICU stay (median, 1 day [range, 1–8] vs 1 day [range, 1–4], P = 0.019). Rates of therapeutic plasma exchange and intravenous lipid emulsion therapy did not differ ( P = 0.483 and P = 0.229, respectively). Implications/Conclusions: In poisoned patients, proper evaluation and management of patients requiring PICU admission are vital for favorable patient outcomes.